(untitled) (World Bulletin of Education and Learning, 2025)
This article explores effective pedagogical strategies for teaching heat conduction in solid bodies, with a focus on using differential equations—particularly Fourier’s law and the resulting heat equation—to enhance conceptual understanding among undergraduate physics students. It outlines theoretical foundations, instructional approaches, visualization techniques, problem solving strategies, and assessment methods. The article also presents sample classroom activities and methodological recommendations to ensure clear comprehension of differential models of thermal processes.